Uji Kelayakan Bukit Cermin Kota Tanjungpinang Provinsi Kepulauan Riau Sebagai Lokasi Rukyatul Hilal - Nofran Hermuzi; M. Arbisora Angkat (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2021)
Bukit Cermin Tanjungpinang City is the location of Rukyatul Hilal which has been used by the Ministry of Religion of Kepulauan Riau Province since 2015. The factor of using Bukit Cermin as the location of Rukyatul Hilal is because it has an observable area of view at azimuth 240o-300o and easy access to the location. The topography of Tanjungpinang is mostly sea/water. So it is easy for evaporation to occur so that clouds often appear in the afternoon, especially on the western horizon when the sun will set and become an obstacle in the implementation of Rukyatul Hilal in Tanjungpinang city. Since 2015 until now, in Bukit Cermin the hilal has never been seen. So, Bukit Cermin is not suitable as a location for Rukyatul Hilal.